Aerodynamics and pollen ultrastructure in Ephedra. Issue 3 (1st March 2015) - Bolinder, Kristina; Niklas, Karl J.; Rydin, Catarina
Abstract : Premise of the study: Pollen dispersal is affected by the terminal settling velocity ( U t ) of the grains, which is determined by their size, bulk density, and by atmospheric conditions. The likelihood that wind‐dispersed pollen is captured by ovulate organs is influenced by the aerodynamic environment created around and by ovulate organs. We investigated pollen ultrastructure and U t of Ephedra foeminea (purported to be entomophilous), and simulated the capture efficiency of its ovules. Results were compared with those from previously studied anemophilous Ephedra species. Methods: U t was determined using stroboscopic photography of pollen in free fall. The acceleration field around an "average" ovule was calculated, and inflight behavior of pollen grains was predicted using computer simulations. Pollen morphology and ultrastructure were investigated using SEM and STEM. Key results: Pollen wall ultrastructure was correlated with U t in Ephedra . The relative proportion and amount of granules in the infratectum determine pollen bulk densities, and (together with overall size) determine U t and thus dispersal capability. Computer simulations failed to reveal any functional traits favoring anemophilous pollen capture in E. foeminea . Conclusion: The fast U t and dense ultrastructure of E. foeminea pollen are consistent with functional traits that distinguish entomophilous species from anemophilous species. In anemophilous Ephedra species, ovulate organs create an aerodynamic microenvironment that directs airborne pollen to the pollination drops. In E. foeminea, no such microenvironment is created. Ephedroid palynomorphs from the Cretaceous share the ultrastructural characteristics of E. foeminea, and at least some may, therefore, have been produced by insect‐pollinated plants.